ECONOMIC EFFICIENCY OF ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN THE SERVICE SECTOR - Nuraliyeva Feruza (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
The article examines the economic aspects of applying artificial intelligence technologies in the service sector within the context of the rapid development of the digital economy. The study analyzes the impact of intelligent digital solutions on improving enterprise efficiency, automating service processes, and enhancing mechanisms of interaction with consumers. Particular attention is paid to the use of analytical platforms, machine learning algorithms, chatbots, and digital services across various areas of the service economy. The research findings indicate that the implementation of AI technologies contributes to reducing time and financial costs, increasing labor productivity, improving service quality, and creating personalized services. At the same time, several factors limiting the widespread adoption of artificial intelligence are identified, including the need to modernize digital infrastructure, the shortage of qualified specialists, and risks related to information security. Based on the results of the study, it is concluded that artificial intelligence is becoming an important tool for increasing the competitiveness of enterprises and promoting the further development of the modern service sector in the conditions of digital economic transformation.